(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The article outlines ways to synthesize the water-soluble catalyst carboxilkoboltcyanin using mellytic acid derived from brown coal deposits in Kyrgyzstan.